Peluang dan Tantangan Penyelesaian Perselisihan Hubungan Industrial melalui Bipartit di Provinsi Kalimantan Timur - Fitriyani, Fitriyani; Pratama, Rio Arif; Surahman, Surahman (IAI Nasional Laa Roiba Bogor, 2025)
The resolution of industrial relations disputes through bipartite mechanisms in East Kalimantan holds potential to establish harmonious, efficient, and fair labor relations. This study aims to analyze the resolution mechanism, identify its effectiveness, and explore the factors influencing its success. Data indicate that this mechanism faces various obstacles, including power imbalances, lack of regulatory understanding, and limited openness among stakeholders. However, with collaboration and capacity building among all parties, the bipartite mechanism can be optimized to resolve industrial relations disputes. This study provides recommendations to enhance regulatory awareness and training, as well as to encourage the establishment of Bipartite Cooperation Institutions within companies.